Teachers’, principals’ and university-based teacher educators’ multiple conceptions of teachers’ professional development - Sapkota, Tara (Frontiers in Education, 2025)
Researchers and scholars of teacher education have sought to explain the conceptions of teachers’ professional development (TPD) through their empirical and seminal works. To contribute to the knowledge base of multiple actors’ conceptions of TPD, this qualitative study investigated lower-secondary school teachers’, principals’ and university-based teacher educators’ conceptions of TPD when teachers participated in professional development interventions. The professional development intervention was a process for the implementation of a decentralized policy in Norway. Data was collected by conducting four focus group interviews with 19 lower-secondary school teachers and 14 individual interviews with seven principals of lower-secondary schools and seven university-based teacher educators from a local university/university college in western Norway. The data was analyzed by using the constant comparative method. The findings show that the participants in the study discerned some shared and some distinct conceptions of TPD. In the shared conceptions of TPD, teachers, principals and university-based teacher educators emphasized the development of knowledge of ongoing education acts, policies and reform among teachers. The development of the knowledge of content and the knowledge of curriculum among teachers were also incorporated in their shared conceptions of TPD. However, in the distinct conceptions of TPD, teachers emphasized the development of their instructional practices and hands-on skills for teaching, and principals and university-based teacher-educators accentuated teachers’ engagement in reflection on practices and continuous learning throughout their teaching careers. The findings have implications for the revision of TPD policies that seek to improve teachers’, principals’ and university-based teacher educators’ professional development practices from their various professional positions. The findings also point to the need for policymakers to acknowledge teachers’, principals’ and university-based teacher educators’ conceptions as the foundation in the selection of TPD contents and processes while designing and implementing new professional development initiatives in the forthcoming educational reforms.